Multiple Access Chua Chaotic Communication system using Real Orthogonal Matrix Approach - Ali Radhi (Engineering and Technology Journal, 2018)
An alternative to traditional Pseudo-Noise (PN)-Sequences, one-dimension (1D) orthogonal chaotic map sequences, and three dimensional (3D) continuous chaotic systems (x,y,z) are generated by orthonormal Gram-Schmidt process. A new Orthogonal Chua Chaotic Sequences OCCSs-based Direct-Sequence/Spread-Spectrum-Code Division Multiple Access (DS/SS-CDMA) system is proposed. The proposed system combines the 3D Chua chaotic system with Real Orthogonal Matrix Approach (ROMA). Comparing to previous sequences, the OCCSs inherit all beneficial features of Chua's Circuit and ROMA scheme, such as the best correlation properties, higher capacity, Low Probability Interception (LPI), reliable security and good orthogonality. The three analytical Bit Error Rates (BERs) expressions for each orthogonal sequence (𝑥̂𝑘,𝑦̂𝑘,𝑧̂𝑘) of OCCSs with three fingers Rake receiver under three-path Rayleigh fading channel with their spreading delays are derived. The correlation properties, capacity, randomness and security of OCCSs are evaluated. The simulations results show that the overall BERs performances, capacity, and security of proposed (𝑥̂𝑘,𝑦̂𝑘) of OCCSs-based DS/SS-CDMA system outperform classical PN , 1D Logistic Map sequences and sequences of 3D Chua’s circuit generated by orthonormal Gram-Schmidt process. The results also showed that at BER 10-4 for single and multi-user transmissions, the proposed OCCSs(𝑥̂𝑘) has achieved gains of 5 and 4 dB respectively in signal-to-noise (SNR) over traditional DS/SS-CDMA based on other sequences in Rayleigh fading channel.